Interval breast cancer is associated with other types of tumors - Felix Grassmann (Nature Portfolio, 2019)
Interval cancer patients are more likely to carry rare gene mutations than screen-detected breast cancer patients. Here, the authors report that interval cancer patients are more likely cancer survivors and are at a greater risk of developing other non-breast tumors.